Karakterisasi Bioplastik Berbahan Kombinasi Pati Jagung dan Tepung Jagung dengan Perekat Poli Vinil Alkohol (PVA) dan Pemlastis Gliserol - Sri Sutanti; Mumpuni Asih Pratiwi; Lucia Hermawati; Lucia Hermawati Rahayu; Handika Gilang Ramadhan (Jurnal Ilmiah Teknik Kimia, 2022)
The much-needed packaging materials are still dominated by synthetic plastics which are difficult to decompose and produce dioxin gas, thus polluting the environment and dangerous for humans. The solution is to use bioplastics. The study aims to determine the characteristics of bioplastics in the ratio (%)  of corn starch to corn flour: 100:0; 80:20; 60:40; 40:60; 20:80; and 0:100. The study used RAL, and descriptive analysis. Starch suspension with a ratio of 1:20 as much as 100g/run was heated at a temperature of 70-80oC for 30 minutes while stirring added with 10% PVA solution and 1 mL of glycerol heated and stirred for 10 minutes, degassed for 10 minutes, molded and dried at 50-60oC for 24 hours. The resulted bioplastics were then characterized for their water resistance, film thickness, degradation, tensile strength, elongation at break, and morphology. The results showed that the addition of corn flour increased water resistance, film thickness, degradation time, tensile strength, and elongation at break. The best results in this study were obtained at a ratio of 0:100.